Gdańsk - Wrzeszcz ul. Grunwaldzka 28-20 / foto Karol Nowaliński. - Nowaliński, Karol (1935- ). (1980)
Przedstawia kamienicę na skrzyżowaniu ulic Bohaterów Getta Warszawskiego i Grunwaldzkiej, ok. 1985 r.